New species and new records of lichen genus Anisomeridium (Müll. Arg.) M. Choisy (Monoblastiaceae) from India - Mishra, Gaurav K.; Maurya, Akhilesh Kumar; Nayaka, Sanjeeva; Upreti, Dalip K. (Plant Science Today, 2024)
A new species Anisomeridium subphaeospermum is described and illustrated in the present article from Uttar Pradesh, India. It is characterized by a UV- (Negative) thallus, 8-spored asci, biseriate, brown, transversally 1-septate and broadly elliptical ascospores. Additionally, 6 species namely A. adnexum, A. americanum, A. quaternarium, A. subnectendum, A. tuckerae and A. uniseriale are reported as new records for Indian lichen biota along with a key of 26 species of the genus currently known from India.